ANALYSIS OF THE STATE OF CREDITING OF SMALL AND MEDIUM BUSINESS BY BANKING INSTITUTIONS OF UKRAINE IN THE CONDITION OF THE COVID-19 PANDEMIC - LARIONOVA, KATERINA; TANASIENKO, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Access to financial resources, especially through bank lending, is an important factor in the development of small and medium-sized businesses. SMEs need such lending due to lack of own funds, income instability, accelerated movement of working capital, locality of resources and narrow markets. Bank credit occupies a leading position in the formation of financial and investment mechanism for SME development.In the current crisis caused by the coronavirus, banks must ensure maximum access of small and medium-sized businesses to credit resources. With the stabilization of the financial situation and the reduction of interest rates to the level of profitability of SMEs, banks' interest in their lending will be accompanied by increasing competition in this area of banking business development.The article analyzes the state of lending to small and medium-sized businesses by banking institutions of Ukraine in the context of the coronavirus pandemic Covid-19. It is established that during 2018-2020 there was a declining trend in the bank lending to small and medium-sized businesses due to the negative impact of the pandemic on the activities of small and medium enterprises. The rating of the best conditions for lending to small and medium enterprises by Ukrainian banks in 2021 is analyzed and bank lending programs are considered. It is noted that as a result of the introduction of quarantine in 2020 and other restrictive anti-epidemic measures to prevent the spread of coronavirus, the banking system has changed somewhat. The amount of government assistance to small and medium-sized businesses in a pandemic and the features of the state program of business support "Affordable loans 5–7–9 %" are considered.
Keywords: bank lending; small and medium business; interest rates; coronavirus pandemic